Autologous platelet concentrate for the treatment of macular hole: a systematic review and meta-analysis - Dillan Cunha Amaral; Mário Luiz Ribeiro Monteiro; Milton Ruiz Alves; Ivar Vargas Belizario; Lucas de Sousa Tebicherane; Raíza Jacometti; José Eduardo Ferreira Manso; Agma Juci Machado Traina; Ricardo Noguera Louzada (Einstein (São Paulo), 2024)
ABSTRACT Autologous platelet concentrates are rich in growth factors and have shown potential for high anatomical success rates in macular hole treatment. However, no systematic review has yet assessed its impact. Therefore, this study aimed to conduct a comprehensive review and meta-analysis on the comparative efficacy and safety of autologous platelet concentrates in treating macular hole. A systematic review of the literature on autologous platelet concentrate therapy for macular hole was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines on September 9, 2023. Databases, including PubMed, the Cochrane Library, Web of Science, and Embase, were queried. A meta-analysis of random effects was performed. Efficacy was evaluated through anatomical closure, reopening of the macular hole at 6 months, average improvement of 2 lines, and visual field loss. Safety was evaluated by monitoring complications. A systematic search of multiple databases identified six studies (three randomized controlled trials and three non-randomized cohort studies) involving 616 patients (626 eyes). Autologous platelets concentrate therapy significantly improved macular hole closure compared to that in the controls (OR=4.35; 95%CI=2.08-9.10; p<0.0001; I²=9%). No significant differences were observed in hole reopening at 6 months, post-operative visual acuity improvement by 2 lines or more, or visual field loss between autologous platelets concentrate and control groups. The overall complication rates were similar between groups. Thus, autologous platelet concentrate therapy shows promise for promoting macular hole closure, particularly in smaller holes. Further research with standardized protocols, prolonged follow-ups, and larger sample sizes is needed to fully understand its benefits and limitations in macular hole closure. Prospero database registration: (https://www.crd.york.ac.uk/prospero/) under ID CRD42023455815.